2006
DOI: 10.1074/jbc.m604916200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Snapshots of Escherichia coli Histidinol Phosphate Phosphatase along the Reaction Pathway

Abstract: HisB from Escherichia coli is a bifunctional enzyme catalyzing the sixth and eighth steps of L-histidine biosynthesis. The N-terminal domain (HisB-N) possesses histidinol phosphate phosphatase activity, and its crystal structure shows a single domain with fold similarity to the haloacid dehalogenase (HAD) enzyme family. HisB-N forms dimers in the crystal and in solution. The structure shows the presence of a structural Zn 2؉ ion stabilizing the conformation of an extended loop. Two metal binding sites were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 44 publications
2
61
1
Order By: Relevance
“…To examine the propensity of HADSF members for hydrolyzing the substrates in the library, the frequency of each substrate being considered a "hit" was computed. Markedly, pNPP was among the most common substrates (ranked eighth) and was used by 30.4% of the enzymes tested. This is instructive, given the fact that pNPP is commonly used to test for generic phosphatase activity.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the propensity of HADSF members for hydrolyzing the substrates in the library, the frequency of each substrate being considered a "hit" was computed. Markedly, pNPP was among the most common substrates (ranked eighth) and was used by 30.4% of the enzymes tested. This is instructive, given the fact that pNPP is commonly used to test for generic phosphatase activity.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in reaction mechanism are reflected by the very diverse turnover rates of IMPase-like and DDDD HPPs. The k cat value for MtHPP is 3.6 s Ϫ1 , whereas HisB-N converts HOLP to HOL nearly 3 orders of magnitude faster, with k cat ϭ 2.14 ϫ 10 3 s Ϫ1 (83). HisB-N also has a ϳ5 times lower K m (54 M) than does MtHPP, making the latter, and all other examples of IMPaselike HPPs, relatively inefficient enzymes.…”
Section: Mthpp and Impases; Comparison Of The Reaction Mechanism-mentioning
confidence: 99%
“…32 Additionally, phosphoryl-aspartate intermediates have been detected by radioactivity measurements in DNA 3 0 phosphatase Tpp1, 33 and in a recent study, Ca 2þ ions were shown to have an inhibitory effect and induce the accumulation of a phosphoryl-aspartate intermediate detected by mass spectrometry in histidinol phosphate phosphatase. 34 …”
Section: Capture Of Phosphoryl Intermediate For Had Superfamilymentioning
confidence: 99%